The Influence of Implementation Warehouse Management System and Competence on Employee Performance of Logistics at PT. Bumimulia Indah Lestari Cikarang - Ririn Uke Saraswati; Amin Amin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of the Implementating Warehouse Management System (WMS) and Competence on the Employee Performance of PT Bumimulia Indah Lestari. The population of this research is all employees in the logistics department, totaling 60 employees.. The sampling technique used is in this research was the census sampling technique which obtained 60 samples. Research data was obtained from questionnaires distributed to respondents. The research method is quantitative using the SPSS 25 software. The research result show that WMS has a partial effect on employee performance, indicated by a T-value of 5.010 > T-table of 1.671 with a significance of 0.00 < 0.05. Competence also has a partial effect on employee performance, with a T-value of 10.853 > T-table of 1.671 and a significance of 0.00 < 0.05. Simultaneous testing shows an F-value of 93.698 > F-table of 3.16 with a significance of 0.00 < 0.05, meaning that the independent variables of WMS and Competence significantly affect the dependent variable of employee performance simultaneously. The coefficient of determination is 0.767 or 76.7%, while the remaining 23.3% is explained by other variables not included in this research model.